Difference of [Ca2+]i Movements in Platelets Stimulated by Thrombin and TRAP: the Involvement of αIIbβ3-Mediated TXA2 Synthesis - Aoki, Toshiaki; Tomiyama, Yoshiaki; Honda, Shigenori; Senzaki, Kayoko; Tanaka, Akito; Okubo, Mitsuru; Takahashi, Fumie; Takasugi, Hisashi; Seki, Jiro (Thrombosis and Haemostasis, 1998)
This study investigated the difference of [Ca2+]i movement in platelets in response to thrombin and TRAP. The involvement of αIIbβ3 in this signaling was also studied. Stimulation of platelets with thrombin at 0.03 U/ml caused platelet aggregation and a two-peak increase in [Ca2+]i. The second peak of [Ca2+]i, but not the first peak was abolished by the inhibition of platelet aggregation with αIIbβ3 antagonists or by scavenging endogenous ADP with apyrase. A cyclooxygenase inhibitor, aspirin, and a TXA2 receptor antagonist, BM13505, also abolished the second peak of [Ca2+]i but not the first peak, although these regents did not inhibit aggregation. Under the same assay conditions, measurement of TXB2 demonstrated that αIIbβ3 antagonists and aspirin almost completely inhibited the production of TXB2. In contrast to thrombin-stimulation, TRAP caused only a single peak of [Ca2+]i even in the presence of platelet aggregation, and a high level of [Ca2+]i increase was needed for the induction of platelet aggregation. The inhibition of aggregation with αIIbβ3 antagonists had no effect on [Ca2+]i change and TXB2 production induced by TRAP. Inhibition studies using anti-GPIb antibodies suggested that GPIb may be involved in the thrombin response, but not in the TRAP. Our findings suggest that low dose thrombin causes a different [Ca2+]i response and TXA2 producing signal from TRAP. Endogenous ADP release and fibrinogen binding to αIIbβ3 are responsible for the synthesis of TXA2 which results in the induction of the second peak of [Ca2+]i in low thrombin- but not TRAP-stimulated platelets.